Potential interaction of sugar intake and tobacco exposure on dental caries in adults-A cross-sectional study from the National Health and Nutrition Examination Survey - Xuewei Niu; Xiaoan Rong; Hantang Sun (Elsevier, 2024)
Background/purpose: We suspected that there might be an interaction between sugar intake and tobacco exposure on the risk of dental caries. The study aimed to investigate the associations of sugar intake or tobacco exposure with the risk of dental caries. Materials and methods: This cross-sectional study obtained data of 18804 participants from National Health and Nutrition Examination Survey (NHANES) between 2011 and 2018. Weighted univariable and multivariable logistic regression models were applied to explore the associations of total sugar intake or tobacco exposure with the risk of dental caries. The relative excess risk of interaction (RERI), attributable proportion of interaction (API), and synergy index (SI) evaluated the interaction between total sugar intake and tobacco exposure on the risk of dental caries. The effect size of odds ratio (OR), and 95% confidence interval (CI) was inputted. Results: The OR of dental caries in adults with cotinine >10 ng/mL was 1.59 (95%CI: 1.38-1.82). The increased risk of dental caries was found in people with total sugar >19.5%E compared to those with total sugar ≤19.5%E (OR = 1.55, 95%CI: 1.34-1.78). Compared to people with cotinine ≤10 ng/mL and total sugar ≤19.5%E, adults with cotinine >10 ng/mL and total sugar >19.5%E were correlated with elevated risk of dental caries (OR = 2.76, 95%CI: 2.29-3.33). The interaction indicators RERI was 0.980 (95%CI: 0.413-1.547), API was 0.355 (95%CI: 0.192-0.517), and SI was 2.250 (95%CI: 1.344-3.767). Conclusion: There might be interaction between sugar intake and tobacco exposure on the occurrence of dental caries in adults.